Volume-outcome relationship in colon cancer surgery: another biased logical short cut towards questionable centralization policies - Violi, Vincenzo; Costi, Renato; De Bernardinis, Massimo; Pavlidis, Clara; Roncoroni, Luigi (Acta Biomedica Atenei Parmensis, 2014)
The association between hospital high volumes and good outcomes after complex surgery has given rise to a worldwide controversial debate. Important and unsolved questions have followed, both theoretical and practical, which could have repercussions on health care and health economic policies, such as the centralization/regionalization of major surgical procedures. We read a recent study on the impact of surgery volumes on short-term outcomes after colon cancer resection in Emilia Romagna, Italy, the same geographic area where we operate. Ten issues were submitted to critical analysis and many sources of planning and methodology bias were identified, which, in our opinion, paradigmatically led to unreliable results, inadequate statistical analysis and deceptive conclusions. Despite the authors’ admitted awareness of their study’s limits, their conclusive message was, surprisingly, that centralization of colon cancer surgery should be substantially encouraged. Unrecognized, systemic biases may easily turn into cognitive biases, into logical short cuts which could confuse healthcare policy-makers. The volume-outcome relationship, in which a direct causal link has never been demonstrated, should not be used as a reliable measure of quality, rather than less implementable process indicators, to address centralization policies. A disregarded negative consequence of centralization could be that non-high-volume centres, after a further progressive workload decrease and depletion in resources and surgical skills, will have to cope with patients in bad general condition and at high risk, who must be treated in emergency or cannot anyway afford the move for age, indigence or severe co-morbidities. Thus, centralization policies might disadvantage the weak segments of the population, thereby moving towards an iniquitous health service.